Gender representation in written essays on cybercrime amongst secondary school students / Kalairani A/P Nadasan - Kalairani, Nadasan (2014)
The objective of the study is to identify the language used by teenagers to describe the female teenage social network users with relation to cybercrimes. It will focus on the choice of words that teenagers use to describe female teenage users who get involved in cybercrime and later identify the causes that lead the female teenage users‟ involvement in cybercrime over the Internet. The research was carried out based on the written essays submitted by the students essay on the following topic; „Why do female teenagers get involved in Cybercrimes?‟ The words that the students used to describe the involvement of teenagers in activities related to cybercrimes in the cyberspace were analysed and tabled as part of the finding. The words, phrases and sentences that were used in the essays were analyzed using the theoretical framework based on the theme proposed by Christie (1986) on “the ideal victims” referring to the female teenagers categorized as vulnerable, defenseless, innocent and worthy of sympathy and compassion. Both qualitative and quantitative methods are used in the study. The data that is obtained is analyzed using Content Analysis. The findings show that the problems that the female teenagers get into are mainly due to lack of parental guidance, love, ignorance and immaturity. It further explains some of the root causes why the female teenagers are vulnerable and get embroiled in cybercrimes. In conclusion the study provides valuable insight to parents, guardians, supervisors and teachers as to what teenagers need in current times when everyone is busy chasing after either materialistic comforts or career success. It also serves as a reminder to everyone concerned that monitoring, counselling and stricter supervision would be required to handle the teenagers and curb their involvement in cybercrime. Finally, the study will aid in further studies of the same nature to understand teenagers better in this ever changing society and cyberspace.